Depressive symptoms among Peruvian adult residents amidst a National Lockdown during the COVID-19 pandemic - Daniel A. Antiporta (BMC Psychiatry, 2021)
Abstract Background Population health and well-being in Latin America, the current epicenter of the COVID-19 pandemic, has been severely affected during the past semester. Despite the growing evidence about the link between the pandemic, its control measures, and mental health worldwide, there is still no regional evidence of the potential mental health impact. We describe the prevalence and distribution of depressive symptoms across demographic and socioeconomic risk factors in the Peruvian population amidst a national lockdown during the COVID-19 pandemic. Methods Cross-sectional study conducted during the community transmission phase and national lockdown in Peru (May 4th–16th, 2020). We recorded 64,493 responses from adult Peruvian residents through an opt-in online questionnaire. All analyses were weighted using raking based on proportions of sociodemographic variables from the last Peruvian census in 2017. The prevalence of depressive symptoms was calculated using the Patient Health Questionnaire (PHQ-9) score of 10 or more. We identified associated demographic and socioeconomic factors by prior mental health diagnosis. Sensitivity analysis considered an alternative cut-off point for depressive symptoms of PHQ-9 ≥ 14. Results A total of 57,446 participants were included in the analytical sample. A third of the participants (n = 23,526, unweighted) showed depressive symptoms in the 2 weeks prior to the study. Participants who reported a previous mental health diagnosis doubled the sample prevalence of depressive symptoms (59, 95%CI 56.7, 61.4%) of those without a prior diagnosis. Psychosocial and functioning reactions were largely more prevalent among females and young adults. A dose-response relationship was found between household income and depressive symptoms across previous mental health diagnosis strata, being as low as 32% less in the wealthiest than the most impoverished group (PR: 0.68, 95%CI 0.58,0.79). Other critical factors associated with a higher burden of depressive symptoms were lower education level, single, unemployed, and chronic comorbidity. Conclusions An increased burden of depressive symptoms and psychosocial reactions has emerged during the COVID-19 pandemic in Peru compared to previous years. The mental health burden disproportionately affects women, the younger population, and those with low income and education. As the country eases the social distancing measures, it is crucial to use local evidence to adjust public health policies and mental health services to the renewed population needs.